Fiscal Policy and Resilience of the Tourism Industry Against the COVID-19 Pandemic - Mulyana, Andy; Ni Wayan Marsha Satyarini; Indarti Diah Palupi; Hilda Oktavana Siregar; Denny Yohanna; Nashirotun Nisa Nurharjanti (Riset Akuntansi dan Keuangan Indonesia, 2023)
The tourism sector is encountering a global crisis as a consequence of the COVID-19 pandemic. This article aimed to identify and analyze the implementation and impact of fiscal policy on the resilience and sustainability of tourism industry businesses in Indonesia amid the COVID-19 pandemic. An exploratory descriptive qualitative method was used in this research through in-depth interviews with tourism sector business actors in Yogyakarta City, Sleman Regency, Bantul Regency, and Magelang Regency on the implementation of fiscal policy of tax relief for relevant tourism business during the pandemic. The results of the research identified the impact of implementing fiscal policy on business resilience in the tourism sector which is more befitting for medium and large business categories, whilemicro and small businesses could only take advantage of fiscal policy in the form of tax relief, which according to participants is transparent, easy to implement, and does not have a detrimental impact on future. This research contributes to theory, practice, and policy by providing an overview of the impact of environmental factors on the sustainability of tourism sector businesses, the government's response to the crisis, the impact of fiscal policy implementation on the resilience of tourism sector businesses, and input for the government in making future policy.